Peran Pengetahuan Gizi terhadap Frekuensi Konsumsi Fast Food dan Status Gizi pada Remaja: Studi Literatur - Raissa Ulima; Joy Elena Simatupang; Laurena Ginting; Vina Gabriella Saragih (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Nutritional problems among adolescents remain a major concern amid the shift in modern lifestyles increasingly influenced by fast food consumption. The rising trend of fast food intake among adolescents reflects a transition toward practicality, yet often lacks nutritional balance. This literature study aims to analyze the relationship between nutritional knowledge, the frequency of fast food consumption, and adolescents’ nutritional status based on a review of 12 national and international journals published between 2019 and 2025. The findings reveal that nutritional knowledge plays a role in shaping eating behavior, although its direct impact on nutritional status is not always significant. Conversely, frequent fast food consumption is more strongly associated with an increased risk of overnutrition due to its high energy, fat, and sugar content. Therefore, nutritional knowledge contributes indirectly by influencing eating habits that subsequently affect adolescents’ nutritional status. Efforts to improve nutritional knowledge should be accompanied by the development of healthy eating habits and supportive environments that promote balanced nutrition among adolescents.